"Fully Conscious of Their Power": Nineteenth-Century Michigan Editors Search for Journalistic Professionalism. Issue 3 (3rd July 2019) - Banning, Stephen A.
Abstract : Recent studies suggest some nineteenth-century editors had an elite professional identity, while others progressed further, actively attempting to professionalize with codes of ethics and university education. Michigan Press Association proceedings were examined from the nineteenth century to better understand concepts of journalistic personal identity. Findings show the Michigan Press Association, while existing in a remote section of the United States at the time, was sophisticated in its operation and aims and valued being seen as professionals in the mold of doctors, lawyers, and clergy. This reveals nineteenth-century journalism professional interest was more widespread than has been previously realized.